Cross-Country Linkages in Europe : A Global VAR Analysis - Sun, Yan (IMF Working Papers; Working Paper ;, 2013)
This paper uses the Global VAR (GVAR) model proposed by Pesaran and others (2004) to study cross-country linkages among euro area countries, other advanced European countries (including the Nordics, the UK, et cetera), and the Central, Eastern and Southeastern European (CESEE) countries. An innovative feature of the paper is the use of combined trade and financial weights (based on BIS reporting banks' external position data) to capture the very close trade and financial ties of the CESEE countries with the advanced Europe countries. The results show strong co-movements in output growth and interest rates but weaker linkages bewteen inflation and real credit growth within Europe. While the euro area is the dominant source of economic influences, there are also interesting subregional linkages, e.g. between the Nordic and the Baltic countries, and a small but notable impact of CESEE countries on the rest of the Europe.